Gene Editing Preserves Visual Functions in a Mouse Model of Retinal Degeneration - Vagni, Paola; Perlini, Laura E.; Chenais, Naïg A. L.; Marchetti, Tommaso; Parrini, Martina; Contestabile, Andrea; Cancedda, Laura; Ghezzi, Diego (Frontiers in Neuroscience, 2019)
Inherited retinal dystrophies are a large and heterogeneous group of degenerative diseases caused by mutations in various genes. Given the favourable anatomical and immunological characteristics of the eye, gene therapy holds great potential for their treatment. Our goal is to validate the preservation of visual functions by viral-free homology directed repair in an autosomal recessive loss of function mutation. We used a tailored CRISPR/Cas9-based gene editing system to prevent retinal photoreceptor death in the Rd10 mouse model of retinitis pigmentosa. We tested the gene editing tool in vitro and then used in vivo subretinal electroporation to deliver it to one of the retinas of mouse pups at different stages of photoreceptor differentiation. Three months after gene editing, the treated eye exhibited a higher visual acuity compared to the untreated eye. Moreover, we observed preservation of light-evoked responses both in explanted retinas and in the visual cortex of treated animals. Our study validates a CRISPR/Cas9-based therapy as a valuable new approach for the treatment of retinitis pigmentosa caused by autosomal recessive loss-of-function point mutations.